Ian Thomas: How to Grow Herbs - Davidson, Alan E (Petits Propos Culinaires, 1993)
Ian Thomas: How to Grow Herbs: Bloomsbury, London, 1992: 96 pp, colour and b/w illustrations by Antonia Enthoven, £8.99.